2009
DOI: 10.1111/j.1469-1809.2009.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Putative Promoter Regions of Hermansky‐Pudlak Syndrome Genes by Means of Phylogenetic Footprinting

Abstract: SummaryHPS is an autosomal recessive disorder characterized by oculocutaneous albinism and prolonged bleeding. Eight human genes are described resulting in the HPS subtypes 1-8. Certain HPS proteins combine to form Biogenesis of Lysosomerelated Organelles Complexes (BLOCs), thought to function in the formation of intracellular vesicles such as melanosomes, platelet dense bodies, and lytic granules. Specifically, BLOC-2 contains the HPS3, HPS5 and HPS6 proteins. We used phylogenetic footprinting to identify con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…In addition, binding sites for ZF5 are enriched in the genetic promoters of clock-regulated genes, as have binding sites for the known BRCA1 interacting TFs; E2F, AP-1 and NF-Y, SP1 and Oct-1 ( 14 , 15 , 47 ). ZF5 binding sites are also enriched in the promoters of Hermansky–Pudlak syndrome genes HPS3, HPS5 and HPS6 ( 48 ); interestingly, this study also found enrichment of Churc1 binding sites within the promoters of these genes. Taken together, this suggests that BRCA1, Churc1, ZF5 and the other BRCA1 interacting TFs mentioned above may exist as a single and/or multiple complex(es) involved in the transcriptional regulation of various genes.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, binding sites for ZF5 are enriched in the genetic promoters of clock-regulated genes, as have binding sites for the known BRCA1 interacting TFs; E2F, AP-1 and NF-Y, SP1 and Oct-1 ( 14 , 15 , 47 ). ZF5 binding sites are also enriched in the promoters of Hermansky–Pudlak syndrome genes HPS3, HPS5 and HPS6 ( 48 ); interestingly, this study also found enrichment of Churc1 binding sites within the promoters of these genes. Taken together, this suggests that BRCA1, Churc1, ZF5 and the other BRCA1 interacting TFs mentioned above may exist as a single and/or multiple complex(es) involved in the transcriptional regulation of various genes.…”
Section: Discussionsupporting
confidence: 65%
“…A transcription factor EB (TFEB) has been reported to be the master regulator of lysosomal biogenesis (Sardiello et al, 2009). Putative promoter regions of HPS genes may be regulated by TFEB or other transcription factors (Palmieri et al, 2011;Stanescu et al, 2009). The well-known function of lysosomes is the degradation of transported cargoes via the endo-lysosomal-trafficking system.…”
Section: Hps Genes In the Biogenesis Of Lysosomesmentioning
confidence: 99%
“…Human Hermansky-Pudlak syndrome 6 (HPS6) is located on human chromosome 10q24.32, and it consists of only one exon (NM_024747), which is ubiquitously expressed in a variety of tissues [13][14][15]. The transcript size of HPS6 is around 2.6 kb, and its open reading frame encodes 775 amino acids, making up an 83.0 kDa protein (NP_079023) without homology to other human proteins [16,17].…”
Section: Introductionmentioning
confidence: 99%